Genome survey of sago palm (Metroxylon sagu Rottboll) - Lim, Leonard Whye Kit; Chung, Hung Hui; Hasnain, Hussain; Gan, Han Ming (Elsevier Inc., 2021)
The sago palm (Metroxylon sagu Rottboll) is a halophytic, underrated starch-producing palm that is both disease resistant and capable of producing a high yield of storage starch. It is deemed the future tree of life as it has a high potential to be cultivated for its starch to solve global food security issues in the future. Due to low scientific interest of this palm, scarcity of its genomic information has halted our comprehension on the mechanism behind its starch biosynthesis as well as salt and disease resistance pathways. In this study, we report on the genome survey and microsatellite analysis of sago palm. Based on the k-mer statistical approach, the sago palm has an estimated genome size of 464 Mbp to 616 Mbp, consisting of 31.9 to 35.7% repetitive sequence. The heterozygosity of the individual sequenced, a true sago palm clonal breed, was 0.63 to 0.66%. A sum of 123,430,321,878 clean bases were yielded from the 124,258,713,300 raw bases. BUSCO analysis revealed that only around 22% of the 1375 single copy plant genes are complete in both sago palm genome scaffolds and contigs whereas the remaining are missing (~45%) and fragmented (~32%). The fragmented genome assembly generated from short-read Illumina data is likely due to the high repetitiveness of the genome. It is recommended that a long-read sequencing to be carried out to improve the genome information of sago palm. The Illumina data generated in this study will be instrumental for polishing the genome assembly generated from a long-read assembly that is known to be error-prone.